Identification, cloning and lactonase activity of recombinant protein of n-acyl homoserine lactonase (aiia) from bacillus thuringiensis 147-115-16 strain. (2014)
Título en español: Identificación, clonación y actividad lactonasa de la proteína recombinante de N-ácil homoserina lactonasa (AiiA) de Bacillus thuringiensis cepa 147-115-16 Short title: N-acyl homoserine lactonase (AiiA) from Bacillus thuringiensis Abstract: The quorum-quenching N-acyl homoserine lactonases are a family of bacterial metalloenzymes that participate in degradation of N-acyl homoserine lactones (AHLs), disrupting the quorum sensing system of gram negative bacterial species. From a collection of Bacillus thuringiensis strains isolated in Colombia from plants and exhibiting toxic activity against lepidopteran insects, 310 bacterial isolates were tested to determine lactonase activity by using biosensor systems in presence of synthetic N-hexanoyl-L-homoserine lactone (C6-HSL) and N-octanoyl-L-homoserine lactone (C8-HSL). From them, 251 strains showed degrading activity to both C6-HSL and C8-HSL, 57% exhibited degrading activity to C6-HSL and 43% to C8-HSL. One B. thuringiensis strain, denoted as 147-115-16, that exhibit high degrading activity to C6-HSL and C8-HSL, was able to attenuate soft rot symptoms in infected potato slices with Pectobacterium carotovorum. This strain contains an homologous of the aiiA gene that was cloned, sequenced and expressed in Esherichia coli DE3. The recombinant protein AiiA147-11516 display activity to C6-HSL, C8-HSL, N-(β-ketocaproyl) (3-O-C6-HSL) and N-3-oxo-dodecanoyl (3-O-C12-HSL). The recombinant strain in the presence of P. caratovorum cultures was able to attenuate the infection, suggesting that it interferes either on the accumulation or response to the AHLs signals. Acording to this data and based on previous report from recombinant AiiA147-11516, this enzyme exhibit activity to wide range of catalytic substrates suggesting its industrial application in the disease control programs by plants transformation.Key words: lactones, Quorum sensing, Quorum quenching, Lactonases, Pectobacterium caratovorumResumen: Las N-acíl homoserina lactonasas son una familia de metaloenzimas bacterianas que participan en la degradación de N-acil homoserina lactonas (AHLs) interrumpiendo el sistema de detección de quórum sensing de bacterias Gram negativas. A partir de una colección de cepas de Bacillus thuringiensis aisladas del filoplano de plantas colombianas que presentaron actividad tóxina contra insectos lepidópteros, 310 fueron probadas para determinar actividad lactonasa mediante el uso de sistemas de biosensores en presencia de N-hexanoilo-L-homoserina lactona (C6-HSL) y la N-octanoilo-L-homoserina lactona (C8-HSL) sintéticas. De estas cepas, el 251 mostraron actividad para ambas lactonas y de estas, el 57% mostró actividad a C6-HSL y el 43% a C8-HSL. Una cepa de B. thuringiensis- denominada 147-115-16- que mostró alta actividad para C6-HSL y C8-HSL, fue capaz de atenuar los síntomas de la pudrición blanda en rodajas de papa infectadas con Pectobacterium carotovorum. Esta cepa contiene un gen homólogo a aiiA, el cual este fue clonado, secuenciado y expresado en Escherichia coli DE3. La proteína recombinante AiiA147-11516 exhibe actividad para C6-HSL y C8-HSL, así como para N-(β-cetocaproil) (3-O-C6-HSL) y N-3-oxo-dodecanoil (3-O-C12-HSL). La cepa recombinante en presencia  de P. caratovorum fue capaz de atenuar la infección, sugiriendo que interfiere con la acumulación o respuesta de las señales AHLs. Según estos datos y basados en el reporte previo sobre la actividad hidrolítica de la proteína recombinante AiiA147-11516, esta enzima posee un actividad contra un amplio número de sustratos lo cual sugiere su aplicación en la industria en el control de enfermedades, mediante la transformación de plantas.Palabras clave: Lactones, Quorum sensing, Quorum quenching, Lactonases,  Pectobacterium caratovorum.